Human trafficking in colonial Vietnam - Lessard, Micheline R. (London : Routledge, 2015)
'Examining the widespread phenomenon of human trafficking in Vietnam during the period of French colonial rule, this book focuses on the practice of kidnapping or stealing Vietnamese women and children for sale in Chinese markets from the 1870s through to the 1940s'--
Includes bibliographical references : pages 139-147 and index.
Keywords: Human trafficking -- Vietnam -- History; Prostitution -- Vietnam -- History; Vietnam -- Social conditions -- 1858-1945.